“At first, I was only a subscriber”: re-mediating food citizens’ solidarity practices through digital technologies - Stehrenberger, Aline; Schneider, Tanja (Frontiers in Sustainable Food Systems, 2023)
In this paper, we explore how digital technologies re-mediate solidarity practices in alternative food networks (AFNs). To do so, the first author conducted an 8-month (auto-)ethnography of a community supported agriculture (CSA) initiative in Switzerland and 12 semi-structured interviews with CSA members. We identified three types of solidarity practices in our analysis that aim to support social inclusiveness, increase responsibility and sustainability, and foster the sharing of risk, work and infrastructure amongst CSA members. Digital technologies are central for joining and becoming a member of the CSA and also play a vital role in sharing information and organizing members’ work assignments. By becoming a member, consumers become subscribers voting with their wallet. If they regularly engage in farm work, they become prosumers or co-producers. Thus, our analysis foregrounds the continuum of food citizenship in the CSA we studied. However, the number of subscribers increases through digital technologies, transforming the initiative from an alternative to the market to an alternative within the market, whereby certain aspects of solidarity, such as social inclusiveness and sharing, are not realized anymore. Our study contributes to the emerging field of digital food studies by showing how solidarity is digitally enabled and negotiated in CSA, and how this shapes food citizenship.